Confusion of tongues: A return to Sandor Ferenczi (2018)
Sandor Ferenczi, Sigmund Freud's brilliant pupil as well as an innovative psychoanalyst, was silenced by various generations of his contemporaries until, in the past decades, his work began to be rediscovered. Certain aspects of his trauma theory, in fact, had never been thoroughly addressed, particularly, the connection he made between trauma and language. Miguel Gutierrez-Pelaez offers a new reading of Ferenczi by proposing a dialogue between the Hungarian psychoanalyst's work, philosophy, and contemporary psychoanalysis. Among the subjects covered, the book delves into the vulnerability of children and Ferenczi’s never-ending search for a cure, the complex issue of war trauma and, more specifically, his anticipatory work in understanding the effects on the human psyche of the horrific experiences in concentration camps during World War II. These issues are raised against the backdrop of captivating figures like Jacques Lacan, Emmanuel Levinas, Giorgio Agamben, Derrida, Nietzsche, and Primo Levi, among others. © 2018 by Miguel Gutiérrez-Peláez.